High Quality Product, Good Services, and Competitive Pricing of Local Coffee Shop to Increase Consumer Satisfaction and Loyalty - Gunawan, Aidin Wahyu; Muhaimin, Abdul Wahid; Sitawati, Riyanti Isaskar (The University of Lampung, 2024)
The objective of this work is to analyze the effect of service quality, product quality and price on the consumer satisfaction and loyalty of “Beli Kopi” at Baureno Village. This research used Structural Equation Modeling (SEM) analysis with a sample of 50 respondents. The results show that most customers were highly educated with high income and women as the main consumers. Service quality, product quality and price have a significant contribution to consumer satisfaction and loyalty. The research model is valid with outer loading > 0.706 and reliable with AVE > 0.874 and improving service quality, product quality and prices in line with consumer values will increase consumer satisfaction and loyalty. It is hoped that this research can provide theoretical and practical contributions in increasing consumer satisfaction and loyalty at “Beli Kopi” Baureno Village. The research also showed that service quality, product and price influence consumer satisfaction. Product quality is the strongest factor. Consumer satisfaction also has a strong influence on loyalty. To increase sales, research suggests that “Beli Kopi” improve service, maintain product quality at appropriate prices, and create attractive promotions. Keywords: Coffee, Price, Product quality, Service quality, SEM (Structural Equation Modeling).